Economic analysis of intercropping Orthosiphon Stamineus with Durio Zibethinus and Hevea Brasiliensis with different organic fertilizer regimes - Aminuddin Mohamad; Affendy Hassan; Roszehan Mohd Idrus; Normah Awang Besar (Universiti Malaysia Sabah, 2010)
Economic analysis on Orthoslphon stamineus Benth. under rubber and durian farm was conducted at Kg. Kogopon, Papar, Sabah. The main objective of this study was to study the economic viability of planting Orthosiphon stamineus (Misai Kucing) in Rubber and Durian farm involving fertilizer application of various types. A Randomized Complete Block Design (RCBD) was used. O. stamineus was planted with spacing 1.5 m between rows and 0.45 m within rows of plants. The site was divided into three (3) blocks or replicates. Each block contained four (4) treatments and 20 plants of O. stamineus for each treatment. Three (3) organic fertilizer treatments were applied to each block excluded control block. Two (2) rates of fertilizer were used and standardized for each fertilizer. In order to conduct the economic analysis, data on yield monthly harvested and recorded to make it per hectare basis. Thus, the approaches for isolating the benefits and costs of Intercropping O. stamineus with Rubber or Durian are based on 'With project' and 'Without project'. Economic criteria such as Net Present Value (NPV), Internal Rate of Return (IRR), Benefit-Cost Ratio (BCR), Payback Period (PBP) and Sensitivity Analysis (SA) were analyzed for 20 years period project. From the computation of 20 years period projection, it is found that the NPV, IRR, BCR and PBP under durian at discounted factor rate 10% were RM91,751.00, 36.57%, 1.05 and 7 years for per hectare basis. Similar result also found under rubber were RM47,413.00, 55.45%, 1.04, 4 years. As a conclusion, the project intercropping of O. stamineus either under rubber and durian indicated economically feasible.